Rekayasa Fasad High Tech pada Selubung Bangunan Pusat Perbelanjaan IT Cyber Mall Malang - Vania Yunike; Wasiska Iyati (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
Globalization era led to a rapid development of technology. IT mall becomes a containerwhich introduce the technology development to the society. There is some mall in Indonesia,which specially concepted as IT building but some of it didn’t built from the first concept sothat the application isn’t on target, especially on façade. Façade have to be the first thingsociety rate for its identity. Cyber Mall, one of the biggest and the most complete IT productmall in Malang experience it. The concept was switched after rebranded. To understand thedesign criteria of commercial IT building, Typology study of IT commercial building,combined with existing and climate response analytics to gain the design criteria of IT mall.The result were three design alternatives which form shading device with their differentcharacteristics in composition, kinetic, color, and form. All were evaluated withquestionnaire to practitioners or architecture academics, and public. From the threealternatives, ACP and curtain wall as the main material which implemented as a secondaryskin with dynamic wavy shape, blue monochrome as the base color, void openings with 80%transparency, and cluster position LED screen at the northeast building side.